Promoting ecotourism product development in Kilim Geopark based on tourists’ perceptions - Yacob, Mohd Firdous; Jaafar, Mastura; Marzuki, Azizan (2013)
Langkawi is currently re-developing its brand as an international geopark tourism spot. Popular for its boating activities, KilimGeopark features its natural as attractions as its main products. With assistance from the government, tourism development helps spur the growth of local businesses. Successful community cooperation in offering services to the visitors is significant in sustaining such development. However, having an annually increasing number of tourists visiting the area has resulted in a dilemma between maintaining the environment’s sustainability and the local community’s economic gains. Given that high economic returns are based on tourist satisfaction, this study explores the levels of clients’ satisfaction with the tourism products and services offered in Kilim. The results indicate that tourists prefer exploring the new ecotourism products being offered. However, as a newly emerging tourism spot, there are many steps that must be undertaken to improve the services. With limitations in the product offered, this study’s results can provide insights to the main stakeholders.